Calcium levels in acid concentrate are critical - A case series of post-hemodialysis hypercalcemia due to high calcium in acid concentrate - Nabadwip Pathak; Sunil Kumar Nanda (Journal of Nephropharmacology)
Introduction: There are very few studies on the discrepancies between prescribed and measured hemodialysis (HD) electrolyte levels, and most of the related studies address discrepancies in dialysate sodium concentrations. To the best of our knowledge, there are no studies on the discrepancy between prescribed and measured dialysate calcium concentrations due to higher-than-expected calcium concentrations in acid concentrates. Objectives: The current study investigated the causes of post-HD hypercalcemia and associated clinical features. Patients and Methods: Due to one episode of post-HD encephalopathy associated with post-HD hypercalcemia, pre- and post-dialysis calcium concentrations were checked with dialysate electrolyte concentrations for all eleven HD patients in the case series. All biochemical and clinical details were collected from hospital records. Paired T-tests and McNamar tests were conducted for statistical analysis of biochemical and clinical variables. Results: A pattern of post-dialysis hypercalcemia was noted in all eleven patients due to a higher measured dialysate calcium concentration (mean ± SD) of 8.591 ± 0.5224 mg/dL as opposed to the prescribed dialysate calcium concentration of 6 mg/dL (1.5 mmol/L). A higher calcium content in the acid concentrate was found to be the reason behind post-dialysis hypercalcemia. The calcium content of the product water of the water treatment plant was found to be within the recommended limits. Future dialysis sessions were performed with HD containing measured calcium, which was within the recommended limits of prescribed dialysate calcium. A significantly greater number of patients who received dialysis with higher calcium dialysate developed intradialytic hypertension than did those who received dialysis with normal calcium dialysate (p=0.031). Conclusion: The discrepancy between the measured and prescribed calcium concentrations may be due to the higher-than-expected calcium concentration in acid concentrate, which can cause post-HD hypercalcemia.